Changes of MDA level and O2 scavenging enzyme activities in wheat varieties as a result of PEG treatment - Király, István; Czövek, Pálma (Acta Biologica Szegediensis, 2002)
The malondialdehyde (MDA) level and the changes of the activity of superoxide dismutases, and peroxidases of two drought resistant Triticum aestivum genotypes and one with high crossing efficiency (Mv9Kr1) were studied under the effect of osmotic stress brought about by PEG in the nutrient solution. There were characteristic differences among the varieties examined in inducible enzymatic activities and maliondialdehyde production reflecting different mechanisms in its stress induced reactions.